2011
DOI: 10.1093/hmg/ddr511
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal neurogenesis generates heterotopias, olfactory micronodules and cortical infiltration following single-cell Tsc1 deletion

Abstract: Neurological symptoms in tuberous sclerosis complex (TSC) and associated brain lesions are thought to arise from abnormal embryonic neurogenesis due to inherited mutations in Tsc1 or Tsc2. Neurogenesis persists postnatally in the human subventricular zone (SVZ) where slow-growing tumors containing Tsc-mutant cells are generated in TSC patients. However, whether Tsc-mutant neurons from the postnatal SVZ contribute to brain lesions and abnormal circuit remodeling in forebrain structures remain unexplored. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 45 publications
11
77
2
Order By: Relevance
“…Figure 1 demonstrates how disruptions in the vast array of developmental processes governed by mTOR signaling in the central nervous system could lead to specific morphologic and physiologic phenotypes that contribute to the development of epilepsy, intellectual and neurocognitive impairment, and other neurological disorders in TSC. 7,10,18-21 63 Zhou et al 66 TSC1 …”
Section: Overview Of Epilepsy In Tscmentioning
confidence: 99%
“…Figure 1 demonstrates how disruptions in the vast array of developmental processes governed by mTOR signaling in the central nervous system could lead to specific morphologic and physiologic phenotypes that contribute to the development of epilepsy, intellectual and neurocognitive impairment, and other neurological disorders in TSC. 7,10,18-21 63 Zhou et al 66 TSC1 …”
Section: Overview Of Epilepsy In Tscmentioning
confidence: 99%
“…The major function of the TSC complex is to repress the activity of Ras homolog enriched in brain (Rheb), the canonical activator of mTOR complex 1 (mTORC1). Thus, loss of Tsc1 in neurons results in hyperactive mTORC1 and morphological changes such as increased soma size and dendritic hypertrophy (Feliciano et al, 2011; 2012; 2013a; Meikle et al, 2007; Neuman and Henske, 2011). To identify dysregulated genes that may contribute to dendritic overgrowth in TSC, we performed a PCR array from conditional Tsc1 knockout mouse tissue and found that the filamin A ( Flna ) transcript was significantly elevated.…”
Section: Introductionmentioning
confidence: 99%
“…The Pten-deficient phenotype also differs from 3429 RESEARCH ARTICLE Pten function in neuroblasts migration defects caused by mutations in other components of the PI3K pathway. Deletion of Tsc1 in the neonatal SVZ, which also activates mTorc1, but induces different feedback signaling compared with Pten loss, caused a decrease in neuroblast migration speed (Huang and Manning, 2009;Feliciano and Bordey, 2012). Deletion of Erbb4, a receptor tyrosine kinase that has been shown to signal through PI3K as well as other downstream pathways, disrupted proper directional orientation, with a significant decrease in the proportion of neuroblasts migrating towards the OB (Anton et al, 2004).…”
mentioning
confidence: 99%